Analisis Penerapan Laporan Keuangan Koperasi Simpan Pinjam dan Pembiayaan Syariah Nur Insani - Varadila Zahra; Diyan Rifqiyah; Rara Nur Aryani; Fortunata A.N. Djagong (Jurnal Bisnis Kreatif dan Inovatif, 2025)
This study aims to analyze the implementation of financial reporting and evaluate the economic performance of Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPPS) Nur Insani during the period from 2022 to 2023. A descriptive qualitative method was employed, utilizing secondary data from the Statement of Financial Position, Cash Flow Statement, and Operating Results Report published by the cooperative. The findings indicate that KSPPS Nur Insani has implemented a computerized financial recording system, which enhances accuracy, transparency, and operational efficiency. However, the cooperative experienced significant financial pressure in 2023, as indicated by decreases in cash and cash equivalents, total assets, and temporary syirkah funds, both short-term and long-term. These declines reflect weakened liquidity and reduced fundraising capacity from members. Despite these challenges, the cooperative succeeded in increasing its Net Operating Results (SHU), demonstrating effective revenue management and operational cost control. Overall, the profitability of KSPPS Nur Insani remains positive, yet strategic improvements are necessary, particularly in strengthening liquidity management, increasing funding sources, optimizing asset utilization, and enhancing digital system implementation to support better financial governance. These strategic efforts are expected to improve business sustainability and maintain member trust in the future.